Pengembangan Komik Berbasis Cerita Rakyat Bengkulu untuk Mensukseskan Gerakan Literasi Sekolah di Sekolah Dasar - Neni Marlianti; Abdul Muktadir; Irwan Koto (UNIB Press, 2023)
This study aims to make GLS a success in elementary schools by presenting comics based on Bengkulu folklore. This type of research is research and development (R&D). The subjects in this study were grade IV, V, and VI students at SDN 04 Bengkulu City. The object of this research is a product in the form of Bengkulu folklore comic media. The research data were analyzed using qualitative data analysis and quantitative data analysis. Quantitative data analysis technique uses quantitative descriptive. The data from the validation results were analyzed using Aiken's V. The results of the research on the validity of the material experts are 1) the content aspect, the index value of V is 1.00, the Aiken correlation coefficient shows that if it is in the range > 0.8 with the